2004
DOI: 10.1290/1543-706x(2004)040<0095:aivsaf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Screening Assay for Inhibitors of Proinflammatory Mediators in Herbal Extracts Using Human Synoviocyte Cultures

Abstract: Tumor necrosis factor-alpha (TNF-alpha), cyclooxygenase (COX)-2, and prostaglandin (PG)E-2 play a critical role in the pathophysiology of arthritis. Tumor necrosis factor-alpha mediates induction of other cytokines, COX-2, PGs, and metalloproteinases, which leads to cartilage degradation. We developed an in vitro human synoviocyte assay system for screening inhibitors of proinflammatory mediators in herbal extracts. Synoviocytes (5 x 10(5) cells/well) obtained during primary knee replacement from osteoarthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 47 publications
2
48
0
5
Order By: Relevance
“…To investigate the chemical component that may be responsible for the anti-inflammatory activities we investigated the effects of the major component (S)- [6]-gingerol on inflammatory pathways in hepatocytes. Our studies and other studies in the literature have shown that ginger extracts suppress inflammation through inhibition of the classical nuclear factor-kappa B (NF-B) pathway in various cell types and tissues [42,47]. Upon exposure to proinflammatory stimuli, activated NF-B directs transcription of target genes [45], including genes encoding cytokines, chemokines, and the enzyme cyclooxygenase 2 (COX2) [48].…”
Section: Effects Of Zingiber Officinale On Inflammatory Markersmentioning
confidence: 59%
“…To investigate the chemical component that may be responsible for the anti-inflammatory activities we investigated the effects of the major component (S)- [6]-gingerol on inflammatory pathways in hepatocytes. Our studies and other studies in the literature have shown that ginger extracts suppress inflammation through inhibition of the classical nuclear factor-kappa B (NF-B) pathway in various cell types and tissues [42,47]. Upon exposure to proinflammatory stimuli, activated NF-B directs transcription of target genes [45], including genes encoding cytokines, chemokines, and the enzyme cyclooxygenase 2 (COX2) [48].…”
Section: Effects Of Zingiber Officinale On Inflammatory Markersmentioning
confidence: 59%
“…On the other hand, the methanol fraction of C. dichotoma bark decreased significantly the gross lesion scores, and production of both TNF-α and PGE 2 . The effect of the methanol fraction on TNF-α may be mediated either by blocking activation of this pro-inflammatory mediator and its transcriptional regulator (Frondoza et al, 2004), and/or inhibits its production from macrophages (Tripathi et al, 2007). Inhibition of PGE 2 , on the other hand, may follow that of TNF-α (Otani et al, 2006), or may result from its ability to inhibit cycloxygenase enzymes (Grzanna et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In human medicine herb hyssop and icelandic lichen are indicated for the treatment of cholelithiasis and cholestasis, thyme herb helps digestion of fat and acts relaxant on the bile ducts, while the saponariae root increases the amount of bile secreted by the liver and facilitate its flow into the duodenum (2,5,14,19). Our study for the first time concerns the relationship between components of Pectosol® and liver pathology.…”
Section: Discussionmentioning
confidence: 96%
“…Pectosol® (composition: saponariae root, herb hyssop, icelandic lichen, thyme herb, extraction solvent 70% etanole and 10 g glycerol) has been used successfully in human medicine to protect the liver during NSAID therapy (14,19). This remedy contain many bioactive compounds with potentially hepatoprotective effects.…”
Section: Introductionmentioning
confidence: 99%